Protection against Pasteurella multocida conferred by an intranasal fowl cholera vaccine in Khaki Campbell ducks - Pichayanut Poolperm; Nisachon Apinda; Yasushi Kataoka; Wittaya Suriyasathaporn; Khajohnsak Tragoolpua; Takuo Sawada; Nattawooti Sthitmatee (The Japanese Journal of Veterinary Research, 2018)
[Abstract] Fowl cholera affects the poultry farming including ducks. The commercial fowl cholera vaccines using parenteral administration are available. Recently, an intranasal fowl cholera vaccines have been developed and tested in layers. This study, we analyzed the biological function of recombinant outer membrane protein H (rOmpH) of Pasteurella multocida strain X-73 and its antiserum. In addition, we also evaluated the protective efficacy in Khaki Campbell ducks. An adhesion inhibition assay on duck embryo fibroblast (DEF) cells was performed demonstrating that rOmpH-immunized duck sera had a potential inhibitory effect on adhesion ability of bacterial strain. An intranasal fowl cholera vaccine was formulated containing 100 μg rOmpH and 3 μg E. coli enterotoxin B (LTB) as an adjuvant. Ducks were intranasally immunized three times at three-week intervals. Challenge exposure was conducted by inoculation at 3.5 × 103 CFU/ml of a strain of X-73 at four weeks after the last immunization. Sera IgY and secretory IgA antibody titers were significantly increased (P < 0.05) post immunization. Lymphocytes from ducks immunized with the rOmpH-LTB-based intranasal vaccine showed higher proliferative response to P. multocida antigens than those from ducks immunized with only rOmpH or LTB (P < 0.05). Protection conferred by immunization with an intranasal or bacterin vaccine in ducks against challenge-exposure were 90% and 80%, respectively. We conclude that the intranasal fowl cholera vaccine protected ducks from artificial P. multocida infection. However, the rOmpH will be formulated with the commercial adjuvant and will be conducted against more P. multocida field strains in the duck flocks.